Laparoscopic treatment of three patients with gastric neuroendocrine tumors.: Case report - Varela Vega, Martín; Barro, Leticia; Baranov, Sofía; Da Rosa, Agustina; Larrosa, Gabriela; Cubas, Santiago; Beraldo, Gerardo; Santiago, Pablo (Cirugía del Uruguay, 2020)
Gastric neuroendocrine tumors constitute 6.9% of all gastrointestinal neuroendocrine tumors and approximately 1% of all gastric neoplasms. They comprise a wide group of tumors that may or may not be secreting, and with very different biological behavior. Although most of them are benign, a small percentage have an aggressive behavior, with metastatic capacity and a poor survival. Given its relatively indolent course, sometimes the diagnosis results from a fortuitous finding, or less commonly when a complication (hemorrhage or obstruction) arises. Upper endoscopy with immunohistochemical analysis of the biopsy is essential for diagnosis. Tomography is the choice for staging. Lymph node dissemination is rare, and lymphatic emptying is not indicated except in cases of undifferentiated tumors or with visible lymphadenopathy intraoperatively, so the laparoscopic approach is especially attractive. The objective of this communication is to present three cases of laparoscopic resolution of gastric neuroendocrine tumors in our department.